Inducible gene manipulations in serotonergic neurons - Weber, Tillmann; Böhm, Gerald; Herrmann, Elke; Schütz, Günther; Schönig, Kai; Bartsch, Dusan (Frontiers in Molecular Neuroscience, 2009)
An impairment of the serotonergic (5-HT) system has been implicated in the etiology of many neuropsychiatric disorders. Despite the considerable genetic evidence, the exact molecular and pathophysiological mechanisms underlying this dysfunction remain largely unknown. To address the lack of instruments for the molecular dissection of gene function in serotonergic neurons we have developed a new mouse transgenic tool that allows inducible Cre-mediated recombination of genes selectively in 5-HT neurons of all raphe nuclei. In this transgenic mouse line, the tamoxifen-inducible CreERT2 recombinase is expressed under the regulatory control of the mouse tryptophan hydroxylase 2 (Tph2) gene locus (177kb). Tamoxifen treatment efficiently induced recombination selectively in serotonergic neurons with minimal background activity in vehicle-treated mice. These genetic manipulations can be initiated at any desired time during embryonic development, neonatal stage or adulthood. To illustrate the versatility of this new tool, we show that Brainbow-1.0LTPH2-CreERT2 mice display highly efficient recombination in serotonergic neurons with individual 5-HT neurons labelling with multiple distinct fluorescent colors. This labelling is well suited for visualization and tracing of serotonergic neurons and their network architecture. Finally, the applicability of TPH2-CreERT2 for loxP-flanked candidate gene manipulation is evidenced by our successful knockout induction of the ubiquitously expressed glucocorticoid-receptor (GR) exclusively in 5-HT neurons of adult mice. The TPH2-CreERT2 line will allow detailed analysis of gene function in both developing and adult serotonergic neurons